PROCESSING AND DISTRIBUTION OF ROTAN CRAFTS PRODUCTS (Calamus sp.) ON SMALL AND MEDIUM ENTERPRISES IN RUMBAI SUBDISTRICT PEKANBARU - Elyasa; Evi Sribudiani; Viny Volcherina Darlis (Jurnal Ilmu Ilmu Kehutanan, 2018)
The rattan craft industry in Pekanbaru City that has been established since 1970s is located in Rumbai Subdistrict. The existence of this industry has been long enough, but until now the picture of the industry pattern of including the production to and the product marketing has not been there. This study aims to determine the origin of raw materials and types of rattan used, the processing of rattan handicrafts from semi-finished goods to finished goods, distribution channels of raw materials, and the marketing of rattan products. This research is done by qualitative descriptive analysis approach. The data were obtained from the results of in-depth interviews, observations, and document studies. The informants were retrieved by purposive sampling technique. Rattan raw materials in the rattan handicraft industry in Rumbai District come from Riau and outside Riau (West Sumatera). The types of rattan used are rattan sega (Calamus caesius), rattan semambu (Calamus scipionum Loureiro), rattan sap (Daemonorops angustifolida Mart), rattan manau (Calamus manau), rattan dahanan (Korthalsia flageris Miq), rattan fitrit of sega and rotan cores of manau type and taboos. Stages of processing rattan handicrafts for furniture in Rumbai Subdistrict consist of modeling, framing, weaving and finishing. As for the webbing consists of determining the model, material measurement, weaving and finishing. Rattan raw material distribution channel consists of farmers collector I collector II processor finished goods processing industry and farmers collector traders processing industry. While the distribution channels and marketing of products used are producers  consumers and producers  retailers  consumers.